2019
DOI: 10.3329/bjar.v44i2.41818
|View full text |Cite
|
Sign up to set email alerts
|

Effect of foliar spray of GA3 and NAA on sex expression and yield of bitter gourd

Abstract: A field experiment was conducted at the Plant Physiology field of Horticulture Research Center, BARI, Gazipur during two consecutive years of kharif 2014 and 2015 to assess the effect of GA3 and NAA on sex expression, yield and yield components of bitter gourd (Momordica charantia L.) var. BARI Karola-1. Eeleven treatments comprising five concentrations each of gibberellic acid (50, 100, 150, 200 and 300 ppm) and naphthalene acidic acid (50, 100, 150, 200 and 300 ppm) along with distilled water considered as c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 5 publications
0
1
0
Order By: Relevance
“…The maximum Vitamin C of Bitter gourd due to treatment might be due to fact that NAA regulate the growth by causing cell division and cell elongation in plant system. These results are in conformity with Khatoon et al [15]. While the minimum value in treatment T0 (control) may owes to its inhibitory effect because this treatment occupy only recommended dose of fertilizers in bitter gourd.…”
Section: Quality Parametersupporting
confidence: 92%
“…The maximum Vitamin C of Bitter gourd due to treatment might be due to fact that NAA regulate the growth by causing cell division and cell elongation in plant system. These results are in conformity with Khatoon et al [15]. While the minimum value in treatment T0 (control) may owes to its inhibitory effect because this treatment occupy only recommended dose of fertilizers in bitter gourd.…”
Section: Quality Parametersupporting
confidence: 92%
“…The combined application of NAA and boron can increase fruit weight due to increased nutrient availability, high nutrient uptake, and photosynthetic rate, all of which boost the fruit output of bottle gourd. Khatoon et al [15]; Fozia et al [16] discovered comparable results in bitter gourd. The longest fruit was found in NAA @ 200 mg/kg+ Boron @ 0.1%, which was shown to be significantly superior to the other treatments.…”
Section: Lengthmentioning
confidence: 81%
“…Tomar and Ramgiry [55] found the best effect of GA3 application on yield per plant was at the concentration of 125 ppm in tomato while another author [56] found a gradual increase in the yield per plant with higher concentration (200 ppm) of GA3. Studies reported that GA3 100 ppm followed by GA3 150 ppm in bitter gourd produced the maximum fruit weight [57] , application of 100 ppm GA3 led to the maximum yield in cucumber [58] . Our present result also supports the authors' depiction of higher yield with a higher concentration of GA3.…”
Section: Discussionmentioning
confidence: 97%